Effectiveness of Intracameral Tissue Plasminogen (r-tPA) Activator in Resolution of Fibrinous Reaction in Refractory Toxic Anterior Segment Syndrome (TASS): Doi: 10.36351/pjo.v40i2.1772 - Bilal Khan; Ahmad, Adnan; Rasul, Javed (Pakistan Journal of Ophthalmology, 2024)
Purpose: To evaluate the effectiveness of tissue plasminogen activator (r-tPA) in resistant toxic anterior segment syndrome (TASS) after Phacoemulsification. Study Design: Quasi experimental. Place and Duration of Study: Khyber Teaching Hospital, Peshawar from August 2021 to August 2023. Methods: Forty-six patients (46 eyes) with an anterior chamber fibrin reaction after cataract surgery were treated with intra-cameral injection of t-PA (30µg/0.1cc) following failure to respond to conventional treatment with intensive topical and subconjunctival steroids. Outcome measures were best corrected visual acuity (BCVA), clearance/recurrence of the fibrin reaction and complications. Results: Intra-cameral t-PA was injected2 to 6 weeks post Phacoemulsification in TASS cases. Mean post-operative injection time was 18.5± 10.2 days. After 1st day post injection, we observed total abolition of fibrinous exudate in 36(78.2%) cases and subtotal resolution in 10 (21.7%) cases. After 6 weeks the TASS was completely settled in 43(93.4%)cases. Mean BCVA improved from 0.59 ± 0.40 log MAR pre-injection to 0.38 ± 0.40 log MAR at 6th week post-injection (p=0.07). There was no statistically significant difference in BCVA and rate of fibrinolysis between the two groups after post r-tPA injections. Intra-cameral r-tPA was not associated with adverse effects like raised IOP or endophthalmitis. Conclusion: Intra-cameral t-PA injection (30µg/0.1cc)appears to be a safe and effective treatment option for resolving anterior chamber fibrin reaction refractory to conventional steroid therapy following cataract surgery.